Nilai-nilai Sosial dalam Novel Terusir Karya Haji Abdul Malik Karim Amrullah dan Implikasinya terhadap Pembelajaran Teks Novel - Bukit, Idemina Br; Afnita, Afnita (Journal of Education Language and Innovation, 2023)
The aims of this research are as to describe the social values and to describe the most dominant social values in the novel Laluir by Haji Abdul Karim Amrullah (HAMKA). This is qualitative research with descriptive method. The data of this research are event units in the form of words, phrases, clauses, or sentences that identify social values in the form of a narrator's narration about characters, actions of characters, and speeches of characters in the background of the novel. The source of the research data is the novel Laluir by HAMKA published by Gema Insani in 2016. The data collection was conducted by reading and understanding the novel, identifying the characters, identifying the event units, and identifying data related to social values in the novel. Overall, 31 data on social values were found in the novel Laluir by Haji Abdul Makil Karim Amrullah. Each of these social values are 10 values of love, 6 values of social responsibility, 5 social values of caring, 6 social values of empathy, and 4 social values of helping. Based on the results of this study, it can be concluded that social values in the novel Laluir by Haji Abdul Makil Karim Amrullah arise because of the speech of the characters and the narrator and the action of taking h in learning the novel text of high school students of class XII.